International Islamic University Malaysia (IIUM) students' perception towards the conduct of Student Representative Council (SRC) election 2014 - Omar, Muhamad Fuzi; Othman, Muhammad Hanif (Globeedu Group, 2015)
The aim of this paper is to evaluate students’ actual experience during the election of Students’ Representatives Council in November 2014. Specifically the paper aims to evaluate the perception of the students towards the conduct of Students Representative Council’s election which was held on November 20, 2014 after a four days campaign. A survey of 21 items was used to analyze the students’ satisfaction after the election. The findings show that the students are satisfied with the conduct of the election for 2014 where the means is above 5. However, there are only three items indicated lower than 5 of the means of the evaluation. First the process of public speaking, second the announcement of the results and third the incentive of 35% book voucher for the voters.